Cognitive Assessment and Enhancement through Video Gaming using Brain Computer Interface (BCI) - Garg, Disha (IJRDO - Journal of Business Management, 2017)
Advancements in biomedical engineering with the use of electrophysiological signals for Electroencephalography (EEG) techniques have led to be more widely used in the diagnosis of brain diseases and in the field of Brain Computer Interface (BCI). BCI is an interfacing system that uses electrical signals from the brain (e.g. EEG) as an input to control applications such as video game. Attention, concentration is the indispensable basis for learning. We found that the attention of the students is reducing day by day. The case of attention decreasing can be found not only within students but also in adults. The aim of this work is to capture and analyze the EEG data from human brain and to enhance their cognitive skills like attention, concentration by giving 20 days mental training on BCI application. Three BCI enabled video games are played before and after the 20 days training session. Humans can control these games using their thoughts. Emotiv headset is used to play the games and signals are recorded when person was playing games in a computer. BCI games are used for this experiment. These games are the special games developed for BCI experiment especially. Various BCI games are available on Emotiv site. These games can be connected automatically with Emotiv software in a computer. Emotiv TestBench software will be used to capture signals and it will also perform analog to digital conversion of the signals. Converted digital data will be processed through signal processing algorithms in Matlab.  Recorded EEG signals contain noise and artifacts. These artifacts have been removed using filters and desirable features are extracted from cleaned signals. The significance of the results is tested using SPSS (Statistical Product and Service Solutions).